Easy and Fast Preparation of TiO2 - based Nanostructures Using Microwave Assisted Hydrothermal Synthesis - Bregadiolli, Bruna Andressa [UNESP]; Fernandes, Silvia Leticia [UNESP]; Oliveira Graeff, Carlos Frederico de [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2017)
TiO2 derivatives with distinct morphologies have been successfully obtained by microwave assisted hydrothermal synthesis in acidic and alkaline medium using mild conditions. Titanium tetraisopropoxide (TTIP) was used as precursor in different environmental conditions under low temperatures, inferior to 150 degrees C, and short synthesis times, from 2 to 60 min. X ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and N 2 adsorption at 77 K (BET) were used to characterize the microstructural properties of the oxides. In the acidic synthesis the reaction time and temperature are not accompanied by significant changes in the structure of the material. However, in the basic conditions, the concentration of Na+ ions strongly influences the particle morphology and growth. The morphology of the nanoparticles shows irregular spheres in acidic conditions, while in alkaline medium, needle like structures are formed as well as aggregated nanotube-like structures synthesized in only 30 min. Besides the difference in the morphology and structure, in both systems, high surface area was obtained.
Keywords: nanostructures; titanium dioxide; microwave assisted hydrothermal synthesis; crystal growth